The Design Thinking in Architectural Project-Applied Research on Urban Design Projects - Dr. Maysoon Muhi Hilal; Maan Sahab Mohammed AL Badri; Seror. Taha. Yaseen; Ola. Younis. Bader (Genius Journals, 2025)
The research attempts to reveal the design thinking that goes on in the designer's mind when he tries to allocate a specific activity inside the architectural project. The research views designing as an explicable process even if the beginner or the professional designers couldn't give convincing reasons for all the decisions they make. The designer is a person who works on the data given to him and produces his design idea through a planned succession of structural analyzing and evaluative steps until he reaches the best possible solutions. Accordingly, the research hypothesizes that activity inside the Architectural project depends on a great extent of design idea development in the designer's mind. The purpose ofthe studywas toreachthe bestdesignmethodfor activity inside the Architectural project through design strategies.
Keywords: Activity; The Designer; Strategies